2023
DOI: 10.3390/polym15061384
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanical Performance Study of Dual Cured Thermoset Resin Systems 3D-Printed with Continuous Carbon Fiber Reinforcement

Abstract: Additive manufacturing (AM) is one of the fastest-growing manufacturing technologies in modern times. One of the major challenges in the application of 3D-printed polymeric objects is expanding the applications to structural components, as they are often limited by their mechanical and thermal properties. To enhance the mechanical properties of 3D-printed thermoset polymer objects, reinforcing the polymer with continuous carbon fiber (CF) tow is an expanding direction of research and development. A 3D printer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Based on the analysis and research of the above curing process parameters, the composite was prepared under −0.09 MPa vacuum degree, 80 min impregnation time and 165°C curing temperature. The flexural strength and modulus of the composite reached 482.89 MPa and 35.11 GPa, respectively, and compared the flexural properties with the 3D printed CCF reinforced polymer composites (CCFRPCs) in literature 21,22,34‐40 . The flexural properties of the 3D printed composites are plotted as shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis and research of the above curing process parameters, the composite was prepared under −0.09 MPa vacuum degree, 80 min impregnation time and 165°C curing temperature. The flexural strength and modulus of the composite reached 482.89 MPa and 35.11 GPa, respectively, and compared the flexural properties with the 3D printed CCF reinforced polymer composites (CCFRPCs) in literature 21,22,34‐40 . The flexural properties of the 3D printed composites are plotted as shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the analysis and research of the above curing process parameters, the composite was prepared under À0.09 MPa vacuum degree, 80 min impregnation time 21,22,[34][35][36][37][38][39][40] The flexural properties of the 3D printed composites are plotted as shown in Figure 11. It can be found that the 3D printed composites in this paper show better flexural properties, which are significantly better than most existing 3D printed CCFRPCs.…”
Section: Demonstration Of 3d Printed Ccfrtcsmentioning
confidence: 99%
“…CFR offers several compelling advantages, including the production of parts that are significantly stronger and lighter than those made from conventional materials, making it ideal for high-performance applications. The technology allows for complex geometries that are difficult to achieve with traditional composite manufacturing techniques, along with reduced waste and shorter production cycles [118]. Additionally, the ability to customize the fiber orientation provides unparalleled control over the mechanical properties of the final part.…”
Section: Advantages and Limitations Of Cfrmentioning
confidence: 99%